Pengaruh Kegiatan Bermain Peran Terhadap Sikap Percaya Diri Anak Usia 5-6 Tahun di TK Al-Ikhlas Kecamatan Mandalawangi - Damayanti, Anisa; Apriliyanti, Dian Surya; Fatimah, Atin (Universitas Pahlawan Tuanku Tambusai, 2025)
Early childhood is children aged 0-8 years, a period characterized as the Golden Age because of the rapid development that occurs during this period. Therefore, appropriate stimulation is very important for optimal child development. Emotional development is an important aspect of child development that requires stimulation. Emotional development is the process by which children learn to identify their feelings and understand various emotions, including sadness, happiness, anger, frustration, empathy, shame, and self-confidence. This study seeks to examine the impact of role-playing exercises on the self-confidence of children aged 5 to 6 years at Al-Ikhlas Kindergarten in Mandalawangi Regency. This study uses a quantitative methodology using a quasi-experimental technique. The research sample consisted of 30 children selected by purposive sampling. Data collection involved observation and experiments, while data analysis used the Paired Sample T-Test with the help of SPSS. The results of the study showed a significant impact of the control class, which was not involved in role-playing activities, compared to the experimental class that did the activity during learning. The control group data showed a significance value (2-tailed) of 0.334. In the experimental group, a value of 0.000 was obtained, thus based on the decision-making criteria if the significance value (2-tailed) exceeds 0.005. This study concludes that role-playing exercises have a significant impact on the self-confidence of children aged 5-6 years at Al-Ikhlas Kindergarten.